Integrated Family Approach in Mental Health Care by Professionals From Adult and Child Mental Health Services: A Qualitative Study - Stolper, Hanna; van Doesum, Karin; Steketee, Majone (Frontiers in Psychiatry, 2022)
Objective: Evaluation by adult and child mental health professionals of a new treatment program that provides an integrated family approach. The treatment focuses on the mental disorders of the parents as well as on the development of the young child and family relationships. This study investigated the added value of this integrated family approach, in which professionals from adult and child mental health services work together. What are the experiences of the professionals involved? Background: Parental mental disorders have an impact on parenting and child development. To stop detrimental cascade effects and prevent parent and child from being caught up in the intergenerational transmission of psychopathology, a family approach to mental health care is needed. It is unusual to integrate the treatments provided by child and adult mental health services. Methods: A qualitative design is adopted using a grounded theory approach. Data were collected through 19 group interviews of professionals from adult and infant mental health teams who worked together in the treatment of a family. Results: Professionals from the two services were comfortable coping with complexity and felt supported to perform their treatments by staying in touch with each other in multi-disciplinary consultations. They indicate that by attuning the treatment components to each other and tailoring them to the capabilities of the family, their treatments had more impact. A flexible attitude of all involved professionals and commitment to the interest of all family members was essential. Conclusion: According to professionals, treatment with an integrated family approach in mental health care is of added value for families by addressing the different roles, positions and relationships and by empowering professionals by multi-disciplinary consultations.